Are voluntary markets effective in replacing state-led support for the expansion of renewables? – A comparative analysis of voluntary green electricity markets in the UK, Germany, France and Italy. (June 2020) - Herbes, Carsten; Rilling, Benedikt; MacDonald, Scott; Boutin, Nathalie; Bigerna, Simona
Abstract: With state-led support being only temporary, attention has turned to retail electricity markets to provide long-term support for renewable electricity. Past research has focused on consumer preferences for green electricity, i.e. the demand side. We investigated the supply side by analyzing what suppliers selling green retail electricity products in the UK, Germany, France and Italy actually provide. Through content analysis of the online data provided by these companies, we found that most products in Germany and France rely on Scandinavian hydropower. Since almost all of these plants have been operating for decades, these products today cannot be said to effectively drive new renewable capacities. Products in the UK and Italy rely on sources which already have state-led support and thus also do not drive the expansion of renewables. In fact, none of the four countries has established a policy framework that successfully fosters the development of a voluntary market for green electricity capable of driving the expansion of renewables. Alignment between sustainable energy policy objectives, consumer demand, and supply-side offerings in a voluntary market might be improved by empowering consumers through a simplified and possibly state-led labeling scheme that focuses on environmental impact and includes minimum standards for performance. Highlights: We examined renewable electricity tariffs in the UK, Germany, France and Italy. Most products in Germany and France are based on Scandinavian hydropower. Eco-labels are used only in Germany, but current practices limit their usefulness. Most products studied do not effectively foster the expansion of renewables. Governments could set minimum standards or provide orientation with eco-labels.